GAYA KOMUNIKASI DALAM BERITA TELEVISI (PRODUKSI PESAN PADA PROGRAM BERITA “POJOK KAMPUNG” JTV DAN PENERIMAAN PESAN DI KALANGAN MASYARAKAT JAWA TIMUR) - Dony Rano Virdaus, (Mediakita, 2019)
The application of regional languages in the news program Kampung Corner JTV is interesting to serve as a study material, where news program Corner Kampung JTV is using the Java Regional Timuran with a “Suroboyo-an” dialect in the news. The uniqueness of the language of Suroboyo-an, which is the local culture of East Java, is packed in a news theme of crime information and the latest info that became one of the Kampung Corner program in JTV. The purpose of this study for: 1). Describe and analyze the communication style from news program “Kampung Kampung” JTV in text level. 2). Describe and analyze the communication style of production the news program message “Kampung Kampung” JTV in the context level. 3). Describe and analyze the communication style of message reception of news program “Kampung Kampung” JTV among East Java society in context level. Aspect of communication in this study for reveal how communication styles are divided into two between high context communication with low context communication in Kampung JTV Corner program with the theory approach presented by Edward T. Hall (1976). The theory of communication style Edward T. Hall does have a close relationship with intercultural communication, it have relation to the mass media of its assessment with low and context context communication approach high. How the mass media perform their duties as a medium of information, convey information to the community with approaches that are closer and friendlier to the culture adopted by the local community. The approach of the theory of message production uses the theory of the construction of social reality which divides into three concepts, namely Externalization, Objectivation, Internalization which is deliver by Peter L. Berger (1966) and also the approach of message reception which divides the three positions, dominant position, oppositional position and negotiation position delivered by Stuart Hall (1980), they will be used by writers to know the production and reception of messages in mass communication news program “Kampung Kampung” JTV in text and context level. This research uses Qualitative method with single case study approach in Kampung Corner program. The research location is located at Surabaya JTV Office. This research was also conducted in Eastern part of East Java (etan) which is Surabaya City and West Java area of West (Kulon) Ponorogo City. 1) the results of the visual and verbal images of the village corner using low context communication style (low context communication) on the message of the crime theme and the latest news 2). Producing contextlevel messages using the construction of social reality with the concept of Internalization on the message of the crime theme and the latest info happening through the language in everyday life that is packed in news programs corner of the village of JTV. Language reflects reality, but simultaneously can create reality, 3). Acceptance of context-level messages visually and verbally news program corner of the village of JTV among the people of East Java Etanan easily accepted and in the East Java community Kulonan use of vocabulary in the Corner Kampung impressed not polite. For the future it is expected that have a cultural communication approach in mass communication to explore communication styles related to message production and message reception of television programs among the people of East Java. And with other methods approach, such as approach of quantitative method or mix method to get the result by data and wide sample. In order that the results of further research will be used as a strong basis valid and can be tested the truth or can made reference by data and methodology.